2021
DOI: 10.1021/acs.langmuir.1c00416
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Remodeling by DNA Origami Nanorods: Experiments Exploring the Parameter Space for Vesicle Remodeling

Abstract: Inspired by the ability of cell membranes to alter their shape in response to bound particles, we report an experimental study of long, slender nanorods binding to lipid bilayer vesicles and altering the membrane shape. Our work illuminates the role of particle concentration, adhesion strength, and membrane tension in determining the membrane morphology. We combined giant unilamellar vesicles with oppositely charged nanorods, carefully tuning the adhesion strength, membrane tension, and particle concentration.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…Importantly, although SLBs do not allow for high-magnitude deformations on a solid support, nanometer-scale deformations are possible, due to the presence of a hydration layer between the support surface and the phospholipid headgroups (Note S1, Supporting Information). [49][50][51] Interestingly, while membrane-mediated interactions of elongated colloidal particles have been previously observed on free-standing lipid bilayers, [23,24] no evidence of membranemediated interactions has been reported for macromolecules and colloidal particles adsorbed on SLBs. [23,[52][53][54][55] A potential reason for that could be that all these experiments were carried out using cationic lipid bilayers strongly adhering to the oppositely charged mica surface via electrostatic attraction.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Importantly, although SLBs do not allow for high-magnitude deformations on a solid support, nanometer-scale deformations are possible, due to the presence of a hydration layer between the support surface and the phospholipid headgroups (Note S1, Supporting Information). [49][50][51] Interestingly, while membrane-mediated interactions of elongated colloidal particles have been previously observed on free-standing lipid bilayers, [23,24] no evidence of membranemediated interactions has been reported for macromolecules and colloidal particles adsorbed on SLBs. [23,[52][53][54][55] A potential reason for that could be that all these experiments were carried out using cationic lipid bilayers strongly adhering to the oppositely charged mica surface via electrostatic attraction.…”
Section: Discussionmentioning
confidence: 96%
“…This results in a stronger interaction of the lipid bilayer with the DNA nanoparticles in comparison with the macromolecules and colloids used in previous studies, and thus allows one to achieve higher surface tension and observe a range of self-organization regimes, which so far has been only achieved in vesicles fully composed of cationic lipids. [24] Although some experiments on interactions of macromolecules with lipid membranes in the gel phase have been carried out previously, [55] these did not allow one to conclude on the existence of membrane-mediated interactions on gel-phase membranes. In these experiments, negatively charged macromolecules were directly electrostatically bound to cationic headgroups of lipid molecules residing in the bilayer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zuraw‐Weston et al reported a similar vesicle deformation triggered by the binding of DNA origami rods. [ 137 ]…”
Section: Molecular Actuation System For Reconfiguration Of Liposomal ...mentioning
confidence: 99%
“…DNA origami is often modified with lipid-membrane binding moieties and is used to directly but statically deform liposomes. [134][135][136][137] As early as 2014, Simmel et al reported rectangular DNA origami modified with cholesterol moieties. [134] They confirmed for the first time that such origami binds to the lipid membrane of GUVs.…”
Section: Liposome Deformation By Membrane-binding Dna Origamimentioning
confidence: 99%